2013
DOI: 10.1093/scan/nst022
|View full text |Cite
|
Sign up to set email alerts
|

Emotional facial expressions reduce neural adaptation to face identity

Abstract: In human social interactions, facial emotional expressions are a crucial source of information. Repeatedly presented information typically leads to an adaptation of neural responses. However, processing seems sustained with emotional facial expressions. Therefore, we tested whether sustained processing of emotional expressions, especially threat-related expressions, would attenuate neural adaptation. Neutral and emotional expressions (happy, mixed and fearful) of same and different identity were presented at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
2
14
3
Order By: Relevance
“…While we did not compare the magnitude of ADA effects between the conditions with neutral and emotional faces, the topography of these effects is quite different from that reported by Gerlicher et al (2014). The SSVEP ADA effect for neutral faces in the Gerlicher et al (2014) study emerged over several occipital electrodes close to the midline, which is different from the more lateralized effect observed in the present study. Therefore, these differences in the spatial distributions of ADA effects across studies presumably reflect different levels of face-related processing.…”
Section: Expressioncontrasting
confidence: 96%
See 2 more Smart Citations
“…While we did not compare the magnitude of ADA effects between the conditions with neutral and emotional faces, the topography of these effects is quite different from that reported by Gerlicher et al (2014). The SSVEP ADA effect for neutral faces in the Gerlicher et al (2014) study emerged over several occipital electrodes close to the midline, which is different from the more lateralized effect observed in the present study. Therefore, these differences in the spatial distributions of ADA effects across studies presumably reflect different levels of face-related processing.…”
Section: Expressioncontrasting
confidence: 96%
“…A recent study using SSVEPs found reduced ADA to facial identity with faces displaying emotional expressions when compared with neutral faces (Gerlicher et al, 2014). While we did not compare the magnitude of ADA effects between the conditions with neutral and emotional faces, the topography of these effects is quite different from that reported by Gerlicher et al (2014).…”
Section: Expressioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In contrast to transient ERPs, ssVEPs elicited by face stimuli allow for a more fine grained examination of individual face discrimination, perceptual face detection (Rossion, 2014), sustained attention and facial expression discrimination (McTeague, Shumen, Wieser, Lang, & Keil, 2011), as well as the interaction of facial expressions and individual face identity (Gerlicher, van Loon, Scholte, Lamme, & van der Leij, 2013). …”
Section: Ssvep Studies Of Socio-emotional Cue Perceptionmentioning
confidence: 99%
“…More precisely, adaptation is strongest for neutral faces and decreases significantly for fearful faces (Gerlicher et al. ), which makes sense from an evolutionary perspective. The aftereffects are thus selectively sensitive to emotions, which further strengthens the point that adaptation acts on the level of the category of emotion, and not on structural differences…”
Section: A Change Of Strategymentioning
confidence: 99%